Audiometric TRT in individuals with DS (Porter et al., 2025) - Heather Porter (13851806) (2025)
Purpose: High rates of hearing loss are observed for individuals with Down syndrome, and regular hearing assessment is recommended for children and adults. Unknown variability of threshold estimates for repeated auditory assessments for individuals with diverse intellectual abilities, such as individuals with Down syndrome, confounds the ability to determine true threshold changes between assessments. This study evaluated variability of pure-tone thresholds measured within and across test sessions for individuals with Down syndrome. Method: Participants included 27 individuals with Down syndrome, ages 5.1–46.5 years (average = 22.7, SD = 11.8). A group of 11 neurotypical individuals, ages 15.9–48.6 years (average = 24.5, SD = 10.3) was included in intrasession variability assessment. Pure-tone thresholds in quiet were measured at 1, 4, 8, and 11.2 kHz during a single session or during repeated audiograms separated by 2.7–11.2 months (average = 5.8, SD = 2.4) and 3.0–3.9 years (average = 3.4, SD = 0.4). Results: Intrasession variability was ≤ 10 dB for 94.3%–100% of thresholds for participants with Down syndrome, with similar variability observed for neurotypical participants. Threshold differences were ≤ 10 dB for 63.2%–85% of responses from audiograms separated by an average of 5.8 months and 37.5%–62.5% of responses separated by an average of 3.4 years. Conclusions: Intrasession variability for participants with Down syndrome aligns with current clinical standards accepting variability of ≤ 10 dB between repeated threshold estimates. Differences in repeated audiometric thresholds greater than 10 dB likely reflect true changes in hearing sensitivity. Supplemental Material S1. A social story depicting all study activities was used to help participants prepare for their visit and familiarize them with study procedures. Each page of the social story includes a figure with a short sentence describing the activity being shown, in this example otoscopy. Supplemental Material S2. A sample visual schedule depicting major study activities. Visual schedules serve as an illustrated checklist and were used to help guide study participation. Porter, H. L., LaSpada, E., Buss, E., & Leibold, L. J. (2025). Test–retest reliability and variability over time for repeated audiometric assessment in individuals With Down syndrome. American Journal of Audiology. Advance online publication. https://doi.org/10.1044/2025_AJA-25-00068